2020
DOI: 10.3389/fpsyg.2020.01158
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Interventions for Developmental Dyslexia: Rhythmic Reading Training Compared With Hemisphere-Specific Stimulation and Action Video Games

Abstract: Developmental dyslexia is a very common learning disorder causing an impairment in reading ability. Although the core deficit underlying dyslexia is still under debate, significant agreement is reached in the literature that dyslexia is related to a specific deficit in the phonological representation of speech sounds. Many studies also reported an association between reading skills and music. These findings suggest that interventions aimed at enhancing basic auditory skills of children with DD may impact readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 55 publications
3
50
0
3
Order By: Relevance
“…Individuals without a formal diagnosis of dyslexia may have not obtained it at the elementary-school level because of a mild severity of their problems and the failure to meet all diagnostic criteria. The formal diagnosis of dyslexia may be a reason for seeking reading comprehension therapy, which may be beneficial to the compensating strategies for dyslexic problems (Cancer et al, 2020;Galuschka et al, 2014Galuschka et al, , 2020Pape-Neumann et al, 2015). People who did not have a formal diagnosis but feel they experience difficulties might be therefore disadvantaged by the fact that they did not receive treatment in the past.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals without a formal diagnosis of dyslexia may have not obtained it at the elementary-school level because of a mild severity of their problems and the failure to meet all diagnostic criteria. The formal diagnosis of dyslexia may be a reason for seeking reading comprehension therapy, which may be beneficial to the compensating strategies for dyslexic problems (Cancer et al, 2020;Galuschka et al, 2014Galuschka et al, , 2020Pape-Neumann et al, 2015). People who did not have a formal diagnosis but feel they experience difficulties might be therefore disadvantaged by the fact that they did not receive treatment in the past.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Cancer et al [ 30 ] compared in a small group of dyslexic children (n = 12) the effect of rhythmic reading training (RRT) on reading speed and accuracy with respect to those of two training types already validated (i.e., Bakker’s visual hemisphere-specific stimulation and the action video game training). Both training types were administrated for 13 h over nine days.…”
Section: Introductionmentioning
confidence: 99%
“…The success of the intervention was not dependent on setting or the musical expertise of participants [15]. Moreover, the efficacy of the RRT was found to be comparable to that of other validated, multimodal approaches [15,17]. Comparative analyses showed that the RRT tended to produce greater effects on reading speed than on reading accuracy.…”
Section: Introductionmentioning
confidence: 99%